Madhwesh G Gudi and Dr. Sunita Dixit - Madhwesh G Gudi and Dr. Sunita Dixit (International journal of economic perspectives, 2022)
Most1the previous studies have focussed on the Micro Finance, Key stakeholders of Micro Finance, participation of SHG and NGO’s, financial inclusion, risk assessment, rate of interest and loan waiver scheme etc., The previous research needs for this study have been determined based on the available literature evaluation in the subject of microfinance organisations and their governance. Microfinance institutions must be adequately regulated and managed. This governance study looks into the various procedures that may be used to control Micro Finance Institutions in order to improve the sector and provide more advantages to Micro Finance Institutions' stakeholders. In this study researcher investigate the procedural elements of the SHG Microfinance Scheme and assess its development, with a focus on the Dharwad district of North Karnataka and also examine the perspectives and perceptions of various SHG players in order to discover the scheme's strong and weak points in order to improve its efficacy. Keywords:- microfinance scheme, bankers, SHG, loaning